Indwelling Catheters Should Be Restricted in Primary and Revision Arthroplasty: A Retrospective Analysis After Changes to Hospital Standard Perioperative Treatment Protocol - Matthias Schnetz; Tim Jakobi; Larissa Ewald; Alexander Klug; Matthias Münzberg; Yves Gramlich (Antibiotics)
Background: Indwelling catheters are used in the perioperative management of patients treated with total joint arthroplasty (TJA) to facilitate fluid control, ease postoperative miction until patients are able to ambulate, and prevent postoperative urinary retention (POUR). However, in TJA, they may be associated with a higher risk of urinary tract infections (UTIs). The aim of the study was to analyze the rates of urinary tract infections and POUR. Methods: Between 2021 and 2022, this study retrospectively identified patients before and after a change in the hospital standard perioperative treatment protocol towards a more restrictive use of indwelling catheters for TJA. In 2021, the use of indwelling catheters involved standard care, but the use was restricted in 2022. Results: A total of 1521 patients were included: 636 patients (41.8%) underwent primary arthroplasty, 646 (42.5%) underwent revision arthroplasty, and 239 (15.7%) underwent hip arthroplasty for femoral neck fractures. Standard use of indwelling catheters significantly decreased from 62.0% to 38.0% (p < 0.001), and the rate of UTI was significantly lower after the protocol change (4.7% vs. 1.2%; p < 0.001). Perioperative urine catheterization was a significant risk factor for UTI (OR = 4.22; p < 0.001), and UTI was a significant risk factor for PJI (OR = 9.99; p < 0.001). POUR increased slightly from 0.9% to 1.8%, but the difference was not significant. POUR was mostly diagnosed following the exchange of the acetabular component in revision arthroplasty (n = 11; 52.4%). Conclusions: Indwelling catheter use was associated with high rates of UTIs. Restricting perioperative use of indwelling catheters was effective in preventing UTIs while causing only a moderate increase in easily treatable postoperative urinary retention. Therefore, the use of indwelling catheters should be avoided in arthroplasty whenever possible.